2020
DOI: 10.3390/cancers12071853
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Mismatch Repair Protein Deficiency in Tumors from Lynch Suspected Cases with Negative Germline Test Results

Abstract: Some 10–50% of Lynch-suspected cases with abnormal immunohistochemical (IHC) staining remain without any identifiable germline mutation of DNA mismatch repair (MMR) genes. MMR proteins form heterodimeric complexes, giving rise to distinct IHC patterns when mutant. Potential reasons for not finding a germline mutation include involvement of an MMR gene not predicted by the IHC pattern, epigenetic mechanism of predisposition, primary mutation in another DNA repair or replication-associated gene, and doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…So, the pathogenic variants do not necessarily appear in one or two specific genes like MLH1 or MSH2 , and even the MSI status can be stable among affected people due to the absence of Knudson's second hit, and further tumor‐specified features will not happen as well, but the pathogen variant can still be passed down to the next generation. In the study of Olkinuora A et al, It was concluded that the analysis of MLH1 and MSH2 genes is not fully trusted, and therefore multi‐gene panels and protein status tests should be considered for all genes 32 . According to our data, females have a higher percentage of MLH1 and MSH2 carriers, which is in line with Muller.…”
Section: Discussionsupporting
confidence: 83%
“…So, the pathogenic variants do not necessarily appear in one or two specific genes like MLH1 or MSH2 , and even the MSI status can be stable among affected people due to the absence of Knudson's second hit, and further tumor‐specified features will not happen as well, but the pathogen variant can still be passed down to the next generation. In the study of Olkinuora A et al, It was concluded that the analysis of MLH1 and MSH2 genes is not fully trusted, and therefore multi‐gene panels and protein status tests should be considered for all genes 32 . According to our data, females have a higher percentage of MLH1 and MSH2 carriers, which is in line with Muller.…”
Section: Discussionsupporting
confidence: 83%
“…Hypotheses were pursued that somatic deletion of the MSH2-MSH6 region and hindered MSH2/MSH6 dimerization would lead to abnormal IHC patterns [ 24 , 25 ]. In this case, one explanation would be proposed that the somatic frameshift mutation, c.3261dupC (p.Phe1088LeufsTer5), within the (C)8 tract in exon 5 of the MSH6 gene attributed to the loss of the MSH2-MSH6 interaction region and reduced MSH6 protein expression, secondary to defective binding to MSH2 protein (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The average base coverage depth for the analyzed samples was 2332. Subsequently, a SALSA MLPA kit P003 from MRC-Holland (Amsterdam, The Netherlands) was used to screen the DNA samples for other large genomic rearrangements in MLH1 as described before [ 26 , 27 ]. A dosage quotient of approximately 0.5 was interpreted as a heterozygous deletion of MLH1 exons.…”
Section: Methodsmentioning
confidence: 99%